Serum microRNAs are early indicators of survival after radiation-induced hematopoietic injury - Acharya, Sanket S; Fendler, Wojciech; Watson, Jacqueline; Hamilton, Abigail; Pan, Yunfeng; Gaudiano, Emily; Moskwa, Patryk; Bhanja, Payel; Saha, Subhrajit; Guha, Chandan; Parmar, Kalindi; Chowdhury, Dipanjan (Science translational medicine, 2015)
Accidental radiation exposure is a threat to human health that necessitates effective clinical planning and diagnosis. Minimally invasive biomarkers that can predict long-term radiation injury are urgently needed for optimal management after a radiation accident. We have identified serum microRNA (miRNA) signatures that indicate long-term impact of total body irradiation (TBI) in mice when measured within 24 hours of exposure. Impact of TBI on the hematopoietic system was systematically assessed to determine a correlation of residual hematopoietic stem cells (HSCs) with increasing doses of radiation. Serum miRNA signatures distinguished untreated mice from animals exposed to radiation and correlated with the impact of radiation on HSCs. Mice exposed to sublethal (6.5 Gy) and lethal (8 Gy) doses of radiation were indistinguishable for 3 to 4 weeks after exposure. A serum miRNA signature detectable 24 hours after radiation exposure consistently segregated these two cohorts. Furthermore, using either a radioprotective agent before, or radiation mitigation after, lethal radiation, we determined that the serum miRNA signature correlated with the impact of radiation on animal health rather than the radiation dose. Last, using humanized mice that had been engrafted with human CD34(+) HSCs, we determined that the serum miRNA signature indicated radiation-induced injury to the human bone marrow cells. Our data suggest that serum miRNAs can serve as functional dosimeters of radiation, representing a potential breakthrough in early assessment of radiation-induced hematopoietic damage and timely use of medical countermeasures to mitigate the long-term impact of radiation.